Evolutionary Psychology and Information Systems Research A New Approach to Studying the Effects of Modern Technologies on Human Behavior - Kock, Ned (Integrated Series in Information Systems,, 2010)
Evolutionary Psychology and Information Systems Research: A New Approach to Studying the Effects of Modern Technologies on Human Behavior is a compilation of chapters written by leading researchers from all over the world. Those researchers' common characteristic is that they have investigated issues at the intersection of the fields of information systems (IS) and evolutionary psychology (EP). The main goal of this book is to serve as a reference for IS research building on EP concepts and theories (in short, IS-EP research). The book is organized in three main parts: Part I focuses on EP concepts and theories that can be used as a basis for IS-EP research; Part II provides several exemplars of IS-EP research in practice; and Part III summarizes emerging issues and debate that can inform IS-EP research, including debate regarding philosophical foundations and credibility of related findings. EP has the potential to become one of the pillars on which IS research can take place. The explanatory power of EP comes from the fact that its underlying ideas relate to the basic design of our brain (and, more generally, our body; including endocrine glands that strongly influence our brain processes and our behavior), and thus can form the basis on which fundamental explanations of behavior in the context of IS design and use can be developed. EP also arguably holds the key to many counterintuitive explanations of behavior toward modern technologies, because many of the evolved instincts that influence our behavior are below the level of our conscious awareness. Often those instincts lead to behavioral responses whose motivations and patterns are not self-evident to the individuals involved - e.g., the fact that we tend to develop vivid memories of facts surrounding a surprising event, whether that event occurs in a real or technology-created (virtual) environment. Integrated Series in Information Systems (IS²) strives to publish scholarly work in the technical as well as the organizational side of the field. This series contains three sub-series including: expository and research monographs, integrative handbooks, and edited volumes, focusing on the state-of-the-art of application domains and/or reference disciplines, as related to information systems.